Pronounced State-Level Disparities in Prescription of Cannabinoids to Medicaid Patients - Edward Y. Liu; Kenneth L. McCall; Brian J. Piper (Medical Cannabis and Cannabinoids, 2023)
Introduction: Dronabinol is approved in the USA for chemotherapy-induced nausea as well as vomiting and HIV-induced anorexia, while cannabidiol is primarily approved for childhood epileptic disorders Lennox-Gastaut and Dravet syndrome. The use pattern for these prescription cannabinoids in the USA is unknown. This study examined Medicaid claims for two FDA-approved prescription cannabinoids, dronabinol and cannabidiol, approved in 1985 and 2018, respectively, from 2016–2020 to better understand the pharmacoepidemiologic trends and distribution of these drugs in US Medicaid amidst the increasing use of non-pharmaceutical formulations of cannabis. Methods: The longitudinal study analyzed Medicaid prescription claims that were calculated by extracting the prescriptions on a state level from 2016 to 2020 for two cannabinoids, dronabinol and cannabidiol, where outcomes over each year were calculated. Outcomes were (1) the number of prescriptions for each state corrected for the number of Medicaid enrollees and (2) dronabinol and cannabidiol spending. Spending refers to the amount reimbursed by the state Medicaid program. Results: Dronabinol prescriptions per state decreased by 25.3% from 2016 to 2020, while cannabidiol prescriptions increased by 16,272.99% from 2018 to 2020. The spending on these drugs parallels that of their prescription trend with a 66.3% decrease in reimbursement for dronabinol ($5.7 million in 2020), whereas cannabidiol increased by +26,582.0% ($233.3 million in 2020). Dronabinol prescriptions, when corrected for the number of enrollees, in Connecticut were 136.4 times larger than in New Mexico, and seventeen states had zero prescriptions. Idaho’s prescriptions of cannabidiol (27.8/10,000 enrollees) were significantly elevated relative to the national average and were 15.4-fold higher than Washington, DC (1.8/10K enrollees). Conclusions: The prescriptions of pharmaceutical-grade tetrahydrocannabinol decreased while those of cannabidiol increased. This study also identified pronounced state-level variation in cannabinoid prescribing to Medicaid patients. State formularies and prescription drug list variation may contribute to the drug reimbursements in Medicaid, though further research is needed to identify the health policy or pharmacoeconomic origins of these disparities.